2019
DOI: 10.1073/pnas.1809037116
|View full text |Cite
|
Sign up to set email alerts
|

Selective auxin agonists induce specific AUX/IAA protein degradation to modulate plant development

Abstract: Auxin phytohormones control most aspects of plant development through a complex and interconnected signaling network. In the presence of auxin, AUXIN/INDOLE-3-ACETIC ACID (AUX/IAA) transcriptional repressors are targeted for degradation by the SKP1-CULLIN1-F-BOX (SCF) ubiquitin-protein ligases containing TRANSPORT INHIBITOR RESISTANT 1/AUXIN SIGNALING F-BOX (TIR1/AFB). CULLIN1-neddylation is required for SCFTIR1/AFBfunctionality, as exemplified by mutants deficient in the NEDD8-activating enzyme subunit AUXIN-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Here we present fluorescent auxin analogues derived from 2,4‐D and labelled with NBD using two different linkers that are attached via the side‐chain carboxyl group of the 2,4‐D with an amide bond. Our concurrent study presenting structures similar to FluorA compounds, being 2,4‐D and 2,4,5‐T derivatives bearing the same PIP linker and a cysteamine aliphatic linker, showed these structures to be sterically favourable for binding to the TIR1‐AUX/IAA7 co‐receptor system in pull‐down assays (Vain et al ., 2019). An extensive SPR analysis revealed that various auxin agonists, including chlorinated auxin derivatives, can differently stabilise the co‐receptor system depending on the F‐box‐AUX/IAA partners, but that IAA conjugates were inactive (Lee et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here we present fluorescent auxin analogues derived from 2,4‐D and labelled with NBD using two different linkers that are attached via the side‐chain carboxyl group of the 2,4‐D with an amide bond. Our concurrent study presenting structures similar to FluorA compounds, being 2,4‐D and 2,4,5‐T derivatives bearing the same PIP linker and a cysteamine aliphatic linker, showed these structures to be sterically favourable for binding to the TIR1‐AUX/IAA7 co‐receptor system in pull‐down assays (Vain et al ., 2019). An extensive SPR analysis revealed that various auxin agonists, including chlorinated auxin derivatives, can differently stabilise the co‐receptor system depending on the F‐box‐AUX/IAA partners, but that IAA conjugates were inactive (Lee et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The TIR and AFB proteins are auxin-sensitive nuclear proteins, which have nucleotide/leucine-rich repeat sites that allow interactions with a specific subset of Aux/IAA proteins (Vain et al, 2019). Studies with Arabidopsis have shown that TIR1/ AFB genes encode major auxin receptors that regulate plant growth, and that AFB3 mediates lateral root growth in response to nitrogen (Vidal et al, 2013).…”
Section: Gene Expression Regulated By Auxinmentioning
confidence: 99%
“…Besides transport, uxin perception is also a key regulating point for apical hook development. Several chemical regulators that target the auxin receptor have been reported, such as auxinole as an antagonist [ 69 ], fluorescent auxin analogs [ 70 ], and selective agonists for specific subsets of AUX/IAA [ 71 ], among which auxinole was applied to dissect the developmental processes of the apical hook [ 15 ]. In addition, an orthogonal auxin–TIR1 receptor pair (convex IAA–concave TIR1) has been developed [ 72 ], providing a strategy for the precise manipulation of auxin signal.…”
Section: Existing Chemical Tools That Could Help Us Understand Apical...mentioning
confidence: 99%